Gender and climate smart agriculture: Co-creating a learning agenda - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
A learning agenda is a set of questions, planned activities and products that facilitate learning and decision making within an organization or project/programme around a specific theme. It is a coordination tool for identifying knowledge gaps and answers a range of priority questions within a given budget and timeframes.